Improvement of continuing medical education - O. V. Sirotkina; T. N. Ischuk; I. S. Golubeva; E. V. Parmon; V. A. Lapotnikov; E. V. Shlyakhto (Российский кардиологический журнал)
The article discusses the issues of paramedic bachelor's degree training in the higher education system. There are no analogues of the paramedic qualification abroad. The significance of the education level for the healthcare quality is shown. The authors demonstrated the key features of the developed educational program of paramedic bachelor's degree training, which includes a large amount of practice.